Murder in chinatown eaudiobook - Thompson, Victoria (Gaslight Mystery, 2008)
Edgar Award finalist Victoria Thompson colorfully portrays the prejudices and hardships of turn-of-the-century New York City. Called to Chinatown to deliver a baby, midwife Sarah Brandt soon helps search for a missing girl. But nobody seems to know where she is. Has she been sold to a brothel, or has she run off with a secret love? ". vividly recreates the gaslit world of Old New York."-Publishers Weekly